Blogs as Objects of Preservation: Advancing the Discussion on Significant Properties - Stepanyan, Karen; Gkotsis, George; Kalb, Hendrik; Kim, Yunhyong; Cristea, Alexandra I.; Joy, Mike; Trier, Matthias; Ross, Seamus (iPress 2012)
challenge for the digital preservation community. While the methodological frameworks for selecting these properties provide a good foundation, a continued discussion is necessary for further clarifying and improving the available methods. This paper advances earlier work by building on the existing InSPECT framework and improving its capabilities of working with complex/compound objects like blogs. The modifications enable a more thorough analysis of object structures, accentuate the differences and similarities between the framework’s two streams of analysis (i.e. Object and Stakeholder analysis) and, subsequently, improve the final reformulation of the properties. To demonstrate the applicability of the modified framework, thepaper presents a use case of a blog preservation initiative that is informed by stakeholder interviews and evaluation of structural and technological foundations of blogs. It concludes by discussing the limitations of the approach and suggesting directions for future research.
Keywords: Blogs; Weblogs; Digital Preservation; Significant Properties